Scientometric Study of Mpox and Vaccine Research: Dynamics, Emerging Patterns, and Networking - Fran Espinoza‐Carhuancho; Juan Alvitez; Abigail Temoche; Victor Roman‐Lazarte; Frank Mayta‐Tovalino (Health Science Reports)
ABSTRACT Background and Aim Mpox (Monkeypox) is a zoonotic disease transmitted through contact with infected animals or humans. Recent research focuses on epidemiology, transmission, and vaccine development to combat its resurgence. This bibliometric study analyzed the dynamics, emerging patterns, and networks of mpox and vaccine research from 2019 to 2024. Methods The literature search was conducted in the Scopus database on August 18, 2024, initially identifying 1278 papers published between January 2019 and August 2024. A specific search strategy was applied to collect documents. The retrieved documents were analyzed using the Scival and Bibliometrix tools to obtain bibliometric metrics. Data analysis was performed using R Studio and Scival. Results During the study period, 562 sources were identified that contributed to 1278 papers on mpox and vaccine research. These papers show an impressive annual growth rate of 91.49%. Several institutions stood out for their contributions to mpox and vaccine research. The journal Vaccines had 58 publications, followed by the Journal of Medical Virology and Vaccine with 31 publications each. According to Bradford's law, in Zone 1, the journal Vaccines had 58 publications. According to Lotka's law, most authors in the field of mpox and vaccine research have written only one article. Conclusion These findings highlight the diversity of sources contributing to the mpox and vaccine research literature and highlight the importance of these sources in terms of their scholarly impact and relevance to the research community. This study provides valuable insight into emerging trends and patterns in the field.